Effect of Catnip Charcoal on the In Vivo Pharmacokinetics of the Main Alkaloids of Rhizoma Coptidis - He, Yanfei (Evid Based Complement Alternat Med, 2016)
This study aims to explore the effect of catnip Nepeta cataria (CNC) charcoal on the pharmacokinetics of the main alkaloids of Rhizoma Coptidis in vivo. Twenty-four rabbits were randomly divided into four groups and given oral administration of an aqueous extract of Rhizoma Coptidis (RCAE), RCAE plus CNC, RCAE plus activated carbon (AC), or distilled water, respectively. Plasma samples were collected after administration. The concentrations of berberine, coptisine, palmatine, and epiberberine in plasma were measured by high-performance liquid chromatography (HPLC). The pharmacokinetics data were calculated using pharmacokinetic DAS 2.0 software. The results showed that the area under the concentration-time curve (AUC) of berberine increased, while the AUC of coptisine, palmatine, and epiberberine decreased in the rabbits that received RCAE plus CNC. Meanwhile, the AUC of berberine, coptisine, palmatine, and epiberberine decreased in the group given RCAE plus AC. The difference of main pharmacokinetics parameters among the four groups was significant (P < 0.05). This study showed that CNC improved the bioavailability of berberine in comparison to AC and prolonged its release in comparison to RCAE alone. However, it decreased the bioavailability of coptisine, palmatine, and epiberberine. In comparison, AC uniformly declined the bioavailability of berberine, coptisine, palmatine, and epiberberine.